2022
DOI: 10.1021/acs.energyfuels.2c01864
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improvement of Water-Based Drilling Mud via Zirconia Nanoparticle/API Bentonite Material

Abstract: Enhanced rheological and mud-filtrate loss characteristics of drilling muds are key to a successful drilling operation. Zirconium dioxide (ZrO2)/clay material (ZCNC) was synthesized using ultrasonication and characterized via scanning electron microscopy (SEM), X-ray diffraction, and Fourier-transform infrared spectroscopy. Moreover, the zeta potential of pristine zirconia and ZCNC was evaluated in distilled water to examine the stability of the colloidal material. Zeta potential measurements revealed that add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…A coating placed to the inside surfaces of subsea oil pipelines may have embedded SPM-NPs, an idea that Mohanty et al, 2022 [131], investigated because of the possibility A relatively new membrane process typically removes multivalent cations and submicronsize natural organic matter [126]. Ceramic NF membranes are becoming more common because of their high chemical, mechanical, and thermal stability.…”
Section: Innovations In Cement Technology: From Self-healing Additive...mentioning
confidence: 99%
See 1 more Smart Citation
“…A coating placed to the inside surfaces of subsea oil pipelines may have embedded SPM-NPs, an idea that Mohanty et al, 2022 [131], investigated because of the possibility A relatively new membrane process typically removes multivalent cations and submicronsize natural organic matter [126]. Ceramic NF membranes are becoming more common because of their high chemical, mechanical, and thermal stability.…”
Section: Innovations In Cement Technology: From Self-healing Additive...mentioning
confidence: 99%
“…A coating placed to the inside surfaces of subsea oil pipelines may have embedded SPM-NPs, an idea that Mohanty et al, 2022 [131], investigated because of the possibility of highly localized and energy-efficient hyperthermia heating. An oscillating magnetic field can be used to create a thin, heated layer of wax (or asphaltene, hydrate) at the interface of the "nano-paint" with the inner pipe surface.…”
Section: Innovations In Cement Technology: From Self-healing Additive...mentioning
confidence: 99%
“…32−35 The use of nanoparticles in drilling fluids is crucial for enhancing the fluid's rheological and thermal transmission characteristics, preserving wellbore stability, and safeguarding oil and gas reserves. 27,36,37 Moreover, nanoparticles are appropriate for the creation of WBDFs with fluid loss agents because of their outstanding adsorption characteristics on amphiphilic polymers. 38,39 Fe 3 O 4 −CMC nanocomposites were studied by Kamali et al to see how they affected the filtration and rheological characteristics of WBDFs.…”
Section: Introductionmentioning
confidence: 99%
“…A new class of materials with distinctive optical, electrical, and mechanical characteristics are called nanomaterials (1–100 nm). Nanomaterials have been researched for use in well drilling and completion, improved recovery, etc. The use of nanoparticles in drilling fluids is crucial for enhancing the fluid’s rheological and thermal transmission characteristics, preserving wellbore stability, and safeguarding oil and gas reserves. ,, Moreover, nanoparticles are appropriate for the creation of WBDFs with fluid loss agents because of their outstanding adsorption characteristics on amphiphilic polymers. , Fe 3 O 4 –CMC nanocomposites were studied by Kamali et al to see how they affected the filtration and rheological characteristics of WBDFs . It was found that Fe 3 O 4 –CMC nanocomposites have superior performance such as a simple synthesis method and are economical compared to CMC.…”
Section: Introductionmentioning
confidence: 99%